Response to Letter to the Editor by Bartoloni et al: 'Interplay of anti‐SSA/SSB status and hypertension in determining cardiovascular risk in primary Sjögren's syndrome'. (5th November 2019) - Mofors, J.; Wahren‐Herlenius, M.; Nordmark, G.
Abstract : Click here to view the Letter to the Editor by Bartoloni et al.